Studi Karakteristik Perpindahan Panas Sirip-Sirip Pin Ellips Susunan Selang-Seling dengan Pendekatan CFD - Syafrudin, Syafrudin; , Marwan Effendy, ST, MT, Ph.D (2016)
This paper describes a performance prediction of the elliptical pin-fin cooling of gas turbine blade. The purpose of this study is to investigate the heat transfer coefficient on the elliptical pin arrangement. The steady RANS with k-epsilon turbulence model was carried-out by two-stages investigation: first, validation of an existing circular staggered array of pin-fin cooling that has been investigated experimentally by other researcher. Three types structured mesh from coarse to fine were optimized for grid refinement study. Second, further investigation of the elliptical pin-fin cooling was simulated by adopting the same scenario of mesh generation based on the optimum result from validation. Simulations were performed at the same initials and boundary conditions as the experiment, and varying Reynolds number from 9,000 to 36,000. The result shows that the heat transfer coefficient is highly influenced by the gas flow condition around the elliptical pin-fin. The increase of Reynolds number intensifies the increase of the heat transfer coefficient.